2016
DOI: 10.1002/adsc.201600686
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Asymmetric Allenylation of Sulfonylimines and Application to the Stereospecific Allylic Allenylation

Abstract: Ther hodium-catalyzeda symmetric allenylation of sulfonylimines is disclosedp roviding silyl homoallenylamide productsi nu pt o9 9:1 er. Through subsequent activation of the C À Nb ondo f the silyl homoallenyl sulfonamide,p alladium-catalyzed stereospecific allylic allenylation could be achieved giving C À Cb ond formation with high chirality transfer.T he synthetic utility of both the silyl homoallenyl sulfonamides andt he silyl homoallenyl malonatesasb is(nucleophiles) is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 76 publications
(19 reference statements)
0
13
0
Order By: Relevance
“…In an effort to further reduce the loading of the boron coupling partner, we next examined other boron derivatives in the coupling reaction in an effort to reduce protodeboronation side-reactions (Scheme 6). Use of the glycol ester ( 16b ) that was optimal in Cammidge’s system 13d and has been recently shown to give improved transmetalation rates in Suzuki-Miyaura cross-coupling reactions 30 gave similar enantioselectivities as that observed with boronic acid 16a but did not afford full conversion in the reaction, even at prolonged reaction times. Use of the pinacol ester 16c allowed for reduction of the boron coupling partner to 2 equiv; however, long reaction times were required and a slight loss in enantiopurity was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to further reduce the loading of the boron coupling partner, we next examined other boron derivatives in the coupling reaction in an effort to reduce protodeboronation side-reactions (Scheme 6). Use of the glycol ester ( 16b ) that was optimal in Cammidge’s system 13d and has been recently shown to give improved transmetalation rates in Suzuki-Miyaura cross-coupling reactions 30 gave similar enantioselectivities as that observed with boronic acid 16a but did not afford full conversion in the reaction, even at prolonged reaction times. Use of the pinacol ester 16c allowed for reduction of the boron coupling partner to 2 equiv; however, long reaction times were required and a slight loss in enantiopurity was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal catalyzed allylic substitution with carbon nucleophiles is a powerful carbon–carbon bond-forming reaction . A number of enantioselective transformations have been realized with various transition metal catalysts including Pd, Mo, W, Ru, Rh, and Ir by employing stabilized carbon nucleophiles such as malonates. For enantioselective allylic alkylation with nonstabilized carbon nucleophiles, Cu catalyst is most frequently employed, allowing the enantioselective installation of simple alkyl groups at the allylic position …”
Section: Introductionmentioning
confidence: 99%
“…Sieber and co-workers 45 reported that the rhodiumcatalyzed enantioselective allenylation reactions of N-tosylimines 74 with the pinacol propargylboronate 5 provided the N-tosyl-α-allenylamines 95 in generally good yields and with good to excellent enantioselectivities (78-98% ee) (Scheme 51). 4-Chlorobenzaldehyde imine only gave a 35% yield (92% ee).…”
Section: Short Review Syn Thesismentioning
confidence: 99%
“…The enyne 130, prepared from the α-allenyl amine 128 underwent a ruthenium-catalyzed cycloisomerization reaction to give the hexahydrocyclohepta[c]pyrrole 131 in 85% yield (Scheme 58). 45…”
Section: Scheme 57 Synthesis Of 13-disubstituted Isoindolines By Basmentioning
confidence: 99%